Drivers of the consumers' intention to use repair services, repair networks and to self-repair. (20th April 2022) - Fachbach, Ines; Lechner, Gernot; Reimann, Marc
Abstract: Repair is a central component of a circular economy to extend the operational phase of products. Yet, the number of repair service providers as well as demand for repair have declined over the last decades, while more products than ever before were sold. Thus, for a successful transition from a linear to a circular economy the demand for repair services must be boosted to promote repair business. A starting point to achieve this goal is to increase knowledge about the end consumers' intention whether to repair broken products or not. An extensive literature research revealed a comprehensive set of drivers of the repair intention covering aspects related to environmental protection, social acceptance, and economic considerations as well as socio-demographic variables, past behaviour, and perceived repair difficulty. Those factors are not only relevant for a specific product category but for repairs of consumer goods in general. The aim is to evaluate the relevance of those drivers for three different repair intentions: (1) to make use of repair service providers, (2) to self-repair broken items, and (3) to use repair service providers incorporated in a repair network. A quantitative online survey was designed, and distributed in Styria, Austria. By means of a structural equation model the acquired data of 900 respondents was analysed. The results emphasise the trade-off between acting environmentally-friendly and economic aspects like repair cost and time, but also highlight the effect of government intervention – in the form of setting up a network and financial support for repair – on shaping this trade-off. Furthermore, past behaviour is found to strongly drive repair intention. Our research contributes to scientific literature by shedding light on the influence of diverse drivers on different repair intentions. It is also relevant for supporting repair companies' decision making with respect to repair service design, as well as public authorities interested in promoting repair. Highlights: We study the repair intention of consumers in Austria with a quantitative survey. Trade-offs between environmental, economic and social repair-decision drivers exist. The existence of a repair network can intervene in the repair decision-making process. Past behaviour is found to strongly drive repair intention. There are disparities between urban and rural areas in the context of repair.